Use of Analytical Hierarchy Process (AHP) in the Environmental Function Recovery Plan for Battery Melting Waste in Bogor Regency: (Case Study on the Restoration of Land Contaminated by Used Battery Smelting Waste in Cinangka and Cinangneng Villages, Bogor Regency) - Gunawan Ismail; Budi Susetyo; Tjahjo Tri Hartono; Haerul Hidayaturrahman; Rimun Wibowo; Ratih Fatima; Sonya Okta Deviro; Sahrul Sidik (Universitas Ibn Khaldun Bogor, 2025)
Environmental pollution caused by unmanaged scrap battery smelting activities in Cinangka and Cinangneng villages, Bogor Regency, has led to heavy metal contamination, particularly lead (Pb), which threatens public health and the ecosystem. This study employs the Analytical Hierarchy Process (AHP) to evaluate four contaminated land remediation methods encapsulation, on-site stabilization and solidification, phytoremediation, and dig and fill based on legal, technical, financial, and environmental aspects. The analysis results indicate that the dig-and-fill method is the best solution for addressing contamination at priority sites with high pollution levels and proximity to residential areas. This method effectively removes contaminated soil and replaces it with pollutant-free soil, thereby minimizing health risks. This study provides strategic recommendations to support land remediation policies in Bogor Regency.